An examination of the gender gap in smartphone adoption and use in Arab countries: A cross-national study. (December 2018) - Ameen, Nisreen; Willis, Robert; Hussain Shah, Mahmood
Abstract: This is the first research to study gender differences among consumers in a cross-national context in the Middle East: the United Arab Emirates (UAE) and Jordan. A conceptual framework was developed by extending the extended unified theory of acceptance and use of technology (UTAUT2) further. It was tested among individuals aged 18–29 years using multi-stage cluster sampling. A total sample of around 900 usable responses from both countries were included in the analysis. The factors national IT development, enjoyment, perceived relative advantage, price value and effort expectancy were found to be significant in the model among Arab women in the UAE and Jordan. The study has theoretical, social and policy relating contributions. The study shows how an extended UTAUT2 fits among both genders in a cross-national context. The study is helpful for policymakers who intend to reduce the gender gap in smartphone adoption and use. The advancement of national IT development and the presence of effective policies focusing on women were found important in both countries. Highlights: Differences between men's and women's adoption of smartphones are revealed. Data was collected from 1066 consumers in Jordan and United Arab Emirates. Enjoyment, effort expectancy, perceived relative advantage and price are important. National IT development and policies are important for empowering women.